Approaching to water quality modeling processes in a subwatershed. The Virilla River case in Costa Rica - Sánchez-Gutiérrez, Rolando (2021)
A surface water quality model was implemented as a first approach to mathematical modeling processes as an input for the integrated management of the middle basin of the Virilla River. The study was conducted in a 20 km-section covering from San Miguel de Santo Domingo to San Antonio de Belén, which is fed by the Tibás River as the main tributary and some discharges of wastewater resulting from various productive activities. The study used a quantitative approach and a MOHID Land model, as well as experimental and historical data of the variables needed for modeling. The model implemented is a numerical program that simulates the dynamics between water-soil and solute transport processes. For purposes of this study, two quality indicators, dissolved oxygen and biochemical oxygen demand, was the concentration modeled. The results obtained in the modeling presented a good adjustment in contrast to the data used for model validation; the error percentages obtained are rated as very good, good, and satisfactory, which can generally be described as an applicable model. Despite this, a more robust calibration needs to be developed along with a sensitivity analysis. There should be a greater dissemination of the use of this tool for the integrated management of water resources in the country. This study serves as a basis for the future modeling of other physicochemical parameters of water bodies, as well as its application in other similar rivers.